PENGEMBANGAN APLIKASI PELATIHAN KELAS KESENIAN DAERAH BERBASIS WEB PADA SANGGAR KASUNDA - Shafar, Muhammad Shafar Alfarizi; S, Mamok Andri; Darsiti, Darsiti; Rusghana, Fadzar (Universitas Lampung, 2025)
The development of a web-based regional arts training application at Sanggar Kasunda aims to enhance administrative efficiency and facilitate information access for both participants and administrators. The system is designed with key features such as online registration, training schedule management, reminder notifications, and an administrative dashboard for data management and evaluation. The development method used is Waterfall, consisting of analysis, design, implementation, and testing phases. The testing results indicate that this application improves efficiency in participant data recording, reduces administrative errors, and accelerates the registration and training management process. With this system, Sanggar Kasunda can more effectively organize training programs and preserve regional arts and culture digitally.